Head Movement Synchrony and Idea Generation Interference – Investigating Background Music Effects on Group Creativity - Hosseini, Sarinasadat; Deng, Xiaoqi; Miyake, Yoshihiro; Nozawa, Takayuki (Frontiers in Psychology, 2019)
Previous studies have indicated that divergent idea integration is an effective way to foster extraordinary creativity in groups. This study posits that background music (BGM) may aid in eliciting this phenomenon. Here to describe the effectiveness of BGM on group creativity, we hypothesized and suggested different mechanisms that genre and valence attributes of BGM would lead to extraordinary creativity. The temporal co-ordination of head movement synchrony (HMS) was investigated as a non-verbal cue and we found significant HMS response levels to idea generation. While the HMS as response did not depend on the quality of the prior ideas; it led to higher divergence and originality in the successively generated ideas. Results of this study showed the dominant contribution of upbeat positive valence music, relative to other genres, in HMS leading to divergent ideas. Following this, the potential role of upbeat music in enhancing participant sociability and positive valence in enhancing cooperation level was discussed. Upbeat positive music may decrease judgmental behavior during creative group tasks and inspire participants to share divergent perspectives. The use of such music can encourage participants to share new perspectives and integrate ideas. It may also provide a potential explanation for the enhancing effect of upbeat positive music on creative outcomes in groups.